2011
DOI: 10.1098/rspb.2011.1549
|View full text |Cite
|
Sign up to set email alerts
|

Pairing dynamics and the origin of species

Abstract: Whether sexual selection alone can drive the evolution of assortative mating in the presence of gene flow is a long-standing question in evolutionary biology. Here, we report a role for pairing dynamics of individuals when mate choice is mutual, which is sufficient for the evolution of assortative mating by sexual selection alone in the presence of gene flow. Through behavioural observation, individual-based simulation and population genetic analysis, we evaluate the pairing dynamics of coral reef fish in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(79 citation statements)
references
References 38 publications
3
76
0
Order By: Relevance
“…The hamlets appear to be able to persist at low densities, which might be due to the fact that they are simultaneously hermaphroditic (implying that two individuals can reproduce regardless of their sex). The hamlets are also able to find conspecifics on the reef when present (Puebla et al, ), which is confirmed here by the observation that three of the four rare species were sighted in pairs when found. Finally, given the data presented here, it is also possible that hamlet distributions might be dynamic at the regional scale over a few decades, which could have implications for the understanding of speciation in this group [population‐centre hypothesis (Domeier, )].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The hamlets appear to be able to persist at low densities, which might be due to the fact that they are simultaneously hermaphroditic (implying that two individuals can reproduce regardless of their sex). The hamlets are also able to find conspecifics on the reef when present (Puebla et al, ), which is confirmed here by the observation that three of the four rare species were sighted in pairs when found. Finally, given the data presented here, it is also possible that hamlet distributions might be dynamic at the regional scale over a few decades, which could have implications for the understanding of speciation in this group [population‐centre hypothesis (Domeier, )].…”
Section: Discussionsupporting
confidence: 85%
“…Relative abundances are not expected to vary seasonally at the reef level since the hamlets are reef‐associated organisms and as such do not move between reefs after settlement (which would imply swimming over extensive non‐reef areas). In addition, transect and tagging data over several seasons at other sites in Panama and Belize (Puebla et al, , ) indicate that hamlet communities do not change substantially at this time scale and that individuals are long‐lived (several years) and quite sedentary. This being said, it is possible that the distribution of individuals within reefs might vary seasonally and the data on depth distribution are therefore to be considered with caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting assortative mating has been widely observed directly or indirectly (using genetic signatures), in both marine and freshwater fishes (Knight & Turner ; Puebla et al . , ; Blais et al . ; Leray et al .…”
Section: Sexual Componentmentioning
confidence: 99%
“…Therefore, although several studies have shown that fish population divergence can be consistent with geographic barriers (Rocha, Bass, Robertson, & Bowen, 2002;Shulman & Bermingham, 1995), an increasing number of studies are reporting results that are more consistent with the role of selection in driving speciation through local adaptation (Rocha & Bowen, 2008;Rocha, Robertson, Roman, & Bowen, 2005b;Taylor & Hellberg, 2005). For example, a number of studies in coral reefs have shown that once gene flow is restricted, niche specialization and sexual selection can readily cause divergence and speciation (Rocha et al, 2005b;Streelman, Alfaro, Westneat, Bellwood, & Karl, 2002;Taylor & Hellberg, 2005) even in the presence of gene flow (Crow, Munehara, & Bernardi, 2010;Puebla, Bermingham, & Guichard, 2012).…”
Section: Introductionmentioning
confidence: 99%